2017
DOI: 10.1016/j.cell.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

NRF1 Is an ER Membrane Sensor that Is Central to Cholesterol Homeostasis

Abstract: Cholesterol is a critical nutrient requiring tight constraint in the endoplasmic reticulum (ER) due to its uniquely challenging biophysical properties. While the mechanisms by which the ER defends against cholesterol insufficiency are well described, it remains unclear how the ER senses and effectively defends against cholesterol excess. Here, we identify the ER-bound transcription factor nuclear factor erythroid 2 related factor-1, Nrf1/Nfe2L1, as a critical mediator of this process. We show that Nrf1 directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
184
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(191 citation statements)
references
References 40 publications
5
184
0
2
Order By: Relevance
“…In cases where SUVs were not used, either 1 µg/reaction 25-OH cholesterol or 5 µg/reaction MBCD:Cholesterol (1:2) was substituted for SUVs. MBCD:Cholesterol was prepared as previously described (Widenmaier et al, 2017). Cholesterol oxidase reactions were performed in Corning 384 well optical imaging plates (#3985) in an ImageXpress MicroXL widefield fluorescence microscope using the TRITC filter sets, where 1 ms exposure time images were taken of each well 20 µm above the well bottom every 10 minutes for 5 hours at 37 °C, using a 10x objective.…”
Section: Fluorometric Cholesterol Oxidase Experiments and Suv Preparamentioning
confidence: 99%
“…In cases where SUVs were not used, either 1 µg/reaction 25-OH cholesterol or 5 µg/reaction MBCD:Cholesterol (1:2) was substituted for SUVs. MBCD:Cholesterol was prepared as previously described (Widenmaier et al, 2017). Cholesterol oxidase reactions were performed in Corning 384 well optical imaging plates (#3985) in an ImageXpress MicroXL widefield fluorescence microscope using the TRITC filter sets, where 1 ms exposure time images were taken of each well 20 µm above the well bottom every 10 minutes for 5 hours at 37 °C, using a 10x objective.…”
Section: Fluorometric Cholesterol Oxidase Experiments and Suv Preparamentioning
confidence: 99%
“…A recent study identified the transcription factor NRF1 as a novel cholesterol sensor that negatively regulates LXR activity when cholesterol levels are low. Upon increase of intracellular cholesterol levels, cholesterol binds NRF1 and releases its inhibition of LXR (Widenmaier et al, ). It is tempting to hypothesize that schweinfurthins might interact with NRF1 or other cholesterol‐sensing proteins.…”
Section: Mechanismmentioning
confidence: 99%
“…On the other hand, one cannot exclude that the pathogenesis of the homozygous PSMC3 variation may involve additional mechanisms. Because target genes of TCF11/Nrf1 include anti-inflammatory factors (Yang et al, 2018;Widenmaier et al, 2017), it is also conceivable that inflammation might play a role in this process. This assumption would be in line with the observation that subjects suffering from other lossof-function proteasome variations such as PSMB8 (Agarwal et al, 2010;Liu et al, 2012;Arima et al, 2011), PSMA3, PSMB4, PSMB9 (Brehm et al, 2015) and/or POMP (Poli et al, 2018) exhibit an inflammatory phenotype including joint contractures.…”
Section: Discussionmentioning
confidence: 99%